Dual-pathological cascade delivery of apoptotic vesicles for targeted therapy in intervertebral disc degeneration - Wei Chen; Tianyuan Zhao; Yiming Ren; Wenzhe Huang; Jiyuan Xia; Zhenxin Hu; Libo Chen; Hao Li; Qi Zhang; Han Wang; Penglei Cui; Quanyi Guo; et al. (Materials Today Bio)
Achieving effective drug delivery and therapeutic efficacy poses significant challenges in intervertebral disc degeneration (IDD). Here, we developed a dual-pathological cascade delivery system utilizing therapeutic mesenchymal stem cell-derived apoptotic vesicles (ApoVs). These vesicles are engineered with MMP13-responsive cell-penetrating peptides (MR-ApoVs) for targeted modulation of senescence. A reactive oxygen species (ROS)-responsive hydrogel incorporating CD44 aptamers (Apt-Gel) was developed to provide high-affinity retention and spatiotemporal controlled release of MR-ApoVs. In this system, MR-ApoV release is first triggered by hydrogel degradation in response to elevated ROS levels. Subsequently, the MMP13-responsive peptides on MR-ApoVs are activated to enhance their internalization into senescent nucleus pulposus (NP) cells, thereby achieving a sequential response to pathological signals within the degenerative disc microenvironment. In a rat model of IDD, MR-ApoV@Apt-Gel effectively attenuated NP cell senescence, restored extracellular matrix homeostasis, preserved disc hydration, and maintained intervertebral disc height. This dual-pathological cascade-responsive strategy represents a promising therapeutic approach for IDD treatment.